ANALISIS FINANSIAL USAHA PETERNAKAN AYAM BROILER DI PETERNAKAN KARISA KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Amrizal Amrizal; Elfi Rahmadani; Elfawati Elfawati (Jurnal Peternakan, 2011)
The objective of the study was to analyze the financial feasibility of the Karisa Broiler Farm based on Net PresentValue (NPV), Benefit Cost Ratio (BCR) and Internal Rate of Return (IRR). The research was conducted on May to June2010 at Karisa Broiler Farm located in Simpang Baru, Tampan, Pekanbaru, Riau. The data consisted of primary data andsecondary data. The primary data consisted of the respondent identity, the general condition of broiler farm, the reveniew, theneed of employee, the sallary of employee, the structure of reveniew, the production factors, the fixed cost and the variablecost. The secondary data was the data from the village office and the sector office. The method was case study. The location ofstudy was choosed directly where the Karisa Broiler Farm was a potentially broiler farm in Pekanbaru. The data was collectedas indept interview using questioner. The respondents were the owner and the employee of Karisa. The data was analyzedusing quantitative descriptive analysis and then showed using financial analysis model throught out project analysisapproach. The result showed that if the Karisa farm use the own capital, where the interest rates was 6,25%, then the NPVwas Rp 274.192.038,8,- and the BCR was 1,12 and if the Karisa farm use the loan capital, where the interest rate was14,5%, then the NPV was Rp 100.583.235,4 and the BCR was 1,06. The IRR of Karisa farm was 22,25%. Based on theeligibility criteria, where the NPV was possitive, the BCR more than one, and the IRR higher than the prevailing interestrate, then the Karisa farm financially feasible to be runed and to be continued.